ASPECTS OF THE BUSINESS SUCCESS IMPORTANT TO FEMALE ENTREPRENEURS IN URBAN AREAS OF THE REPUBLIC OF SERBIA – A PILOT STUDY - Stošić, Danijela (Economic Annals, 2016)
The paper presents results of an empirical study of the importance of qualitative and quantitative dimensions of business success for female entrepreneurs in the Republic of Serbia. There is empirical evidence that qualitative components, such as customer and employee satisfaction, relations with stakeholders, and family-work balance are more important to Serbian female entrepreneurs. Quantitative components (profit and employment growth, personal wealth, and other personal goals), although lower ranked, are also an important aspect of business success. These results also confirm that female entrepreneurs in Serbia have a diverse perception of business success.